BUSINESS COMMUNICATION AS A MANAGEMENT TOOL IN AFTER-SALES AND COLLECTIONS - Aparecida de Almeida, Mariana; Elaine Benetelli Geron, Regina (Revista Gênero e Interdisciplinaridade, 2025)
This study set out to examine business communication as a management tool in after-sales and collection activities. The research was bibliographic and qualitative in nature, drawing on classical authors, recent academic contributions and market reports on organizational relationship practices. The analysis highlighted recurring challenges, such as the lack of structured follow-up after sales, the difficulty in obtaining customer feedback, misalignment among internal areas, and ineffective or overly rigid collection approaches. These shortcomings were found to compromise customer loyalty, generate operational inefficiencies and weaken corporate image. On the other hand, the literature and practical cases pointed to effective alternatives, including the adoption of standardized communication protocols, the use of CRM systems, continuous training of teams, closer integration across departments and the definition of performance indicators. Well-known examples, such as Magazine Luiza, Amazon, Nubank and Itaú Unibanco, illustrate how structured and empathetic communication strategies can lead to greater customer satisfaction, stronger loyalty and improved process efficiency. Therefore, it is concluded that business communication, when strategically applied, represents a competitive advantage capable of strengthening relationships, reducing failures and supporting the financial sustainability of organizations.